How Do External Sector Dynamics Induce Domestic Inflation? : An Econometric Analysis for Bangladesh - Sayed, Imam Abu; Bindu, Rifat Ara; Ferdoush, Romana (Finance & Economics Review, 2025)
Purpose: The Bangladeshi economy has recently experienced elevated inflationary pressures, which have significant implications for economic stability and growth. The purpose of this study is to identify the dynamics of the spillover effects of the external sector on domestic inflation in Bangladesh. Methods: The Autoregressive Distributed Lag (ARDL) approach is deployed for the estimation process, utilizing monthly secondary data from January 2015 to October 2024, available from various sources such as the Bangladesh Bureau of Statistics (BBS), Bangladesh Bank (BB), Food and Agriculture Organization (FAO), and the World Bank (WB). In this analysis, the Consumer Price Index (CPI) is treated as the dependent variable. In contrast, the key explanatory variables include the world oil price, the world food price, exports, imports, and inward remittances. Additionally, industrial production and broad money (M2) are included as control variables, and ‘crisis’ as a dummy variable. Results: The empirical findings confirm that external factors, particularly global oil prices, food prices, and trade dynamics, have a significant influence on Bangladesh’s inflation. A 1 percent rise in past CPI leads to a 0.7 percent rise in the current CPI, revealing strong inflationary inertia. Additionally, global oil price fluctuations have a statistically significant effect on inflation, while the impact of world food prices is delayed, suggesting a lagged transmission into domestic inflation. Trade variables also play a crucial role—exports contribute to inflationary pressures over time mainly due to inequitable growth, whereas imports exert a deflationary effect by reducing supply-side constraints. Additionally, higher domestic industrial production helps mitigate inflation, supporting the supply-side argument, whereas the broad money supply (M2) influences inflation with a lag, reflecting the delayed transmission of monetary policy. Interestingly, remittances have an insignificant direct effect on CPI, implying that while they boost household purchasing power, their inflationary impact is minimal. Furthermore, economic crises, including the COVID-19 pandemic, do not exert a statistically significant independent effect on inflation, reinforcing the dominance of structural economic conditions over short-term shocks. Implications: Basically, the excessive dynamic forces of inflation need to be discounted to zero (thrust level), considering the static force. According to this empirical analysis, external economic factors have a significant impact on creating inflationary pressures in Bangladesh. Originality: This paper provides a unique investigation into the impact of external sector dynamics, including world oil and food prices, exports, imports, and remittances, on domestic inflation in Bangladesh, utilizing the ARDL approach with monthly data from 2015 to 2024. Unlike prior studies, it incorporates both immediate and lagged effects of external variables and accounts for inflationary inertia in a comprehensive empirical framework. Limitations: Although the study provides valuable insights into the external drivers of inflation, it is limited by the exclusion of key fiscal variables, such as the fiscal deficit, due to the unavailability of monthly data. Additionally, the model does not account for nonlinear or asymmetric effects, and structural breaks, such as significant policy shifts, are not explicitly considered in the analysis.